Influence of the Characteristics of Internal Auditors and Management Support on the Effectiveness of Internal Audit - Henny Zurika Lubis; Desi Andriani Lubis (Journal of International Conference Proceedings (JICP), 2022)
This study aims to empirically examine the effect of internal auditor characteristics and management support on the effectiveness of internal audit. This study uses independent variables, namely the characteristics of internal auditor and management support, while the dependent variables is the effectiveness of internal audit. This research is associative quantitative research. The sample of this research is the internal auditors and Supervisors of Regional Government Affairs Organizers who work at Medan City Inspectorate. The sample is done by random sampling method. Data was collected using a questionnaire distributed as many as 57 questionnaires. Statistical method using Multiple Linear Analysis, with hypothesis testing statistical test t. The results of this study indicate that the characteristics of internal auditors do not affects the effectiveness of internal audits, management support affects the effectiveness of internal audits characteristics of internal auditors and management support empirically affect the effectiveness of internal audit Keywords: Auditor, Internal Audit, Management Support.